2006
DOI: 10.2460/javma.229.12.1924
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between computed tomography, magnetic resonance imaging, and surgical findings in dogs with degenerative lumbosacral stenosis

Abstract: Results indicate that there is a high degree of agreement between CT and MRI findings in dogs with degenerative lumbosacral stenosis but that the degree of agreement between diagnostic imaging findings and surgical findings is lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
49
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 35 publications
11
49
0
4
Order By: Relevance
“…The results suggested that survey radiography of the GSD lumbosacrum was not predictive of the development of LS disease, although the rostral projection of the sacral lamina was not specifically evaluated. In our population, the sacral canal height (at the rostral entrance to the canal) was not significantly different between affected and unaffected dogs, which is in agreement with the findings of Scharf et al that the height of the vertebral canal at L7/S1 is neither diagnostic nor predictive for DLSS …”
Section: Discussionsupporting
confidence: 93%
“…The results suggested that survey radiography of the GSD lumbosacrum was not predictive of the development of LS disease, although the rostral projection of the sacral lamina was not specifically evaluated. In our population, the sacral canal height (at the rostral entrance to the canal) was not significantly different between affected and unaffected dogs, which is in agreement with the findings of Scharf et al that the height of the vertebral canal at L7/S1 is neither diagnostic nor predictive for DLSS …”
Section: Discussionsupporting
confidence: 93%
“…Lumbosacral misalignment has been considered to be a sign of instability by several authors, 19,20 whereas others found no significant differences between affected and unaffected dogs. Lumbosacral misalignment has been considered to be a sign of instability by several authors, 19,20 whereas others found no significant differences between affected and unaffected dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced imaging, such as computed tomography (CT) and magnetic resonance imaging (MRI), allows observation of the complex lumbosacral anatomy in multiple planes. However, degenerative lumbosacral changes in dogs without clinical signs and discrepancies between clinical/surgical and CT/MRI findings have been reported and therefore, findings obtained using these advanced imaging techniques should be interpreted with caution . Considerable degenerative changes in the spine of asymptomatic humans have also been reported …”
mentioning
confidence: 99%